2010
DOI: 10.1186/cc9327
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of procalcitonin decrease in patients with severe sepsis: a prospective observational study

Abstract: IntroductionThis prospective study investigated the predictive value of procalcitonin (PCT) for survival in 242 adult patients with severe sepsis and septic shock treated in intensive care.MethodsPCT was analyzed from blood samples of all patients at baseline, and 155 patients 72 hours later.ResultsThe median PCT serum concentration on day 0 was 5.0 ng/ml (interquartile range (IQR) 1.0 and 20.1 ng/ml) and 1.3 ng/ml (IQR 0.5 and 5.8 ng/ml) 72 hours later. Hospital mortality was 25.6% (62/242). Median PCT concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 50 publications
7
95
3
3
Order By: Relevance
“…This was in accordance with the reports of Karlsson et al 18 and Andreola et al 19 though the rate of positive culture was less than ours. Karlsson et al18 also reported of significantly higher PCT levels in positive culture cases compared to that of the negative ones.…”
supporting
confidence: 80%
“…This was in accordance with the reports of Karlsson et al 18 and Andreola et al 19 though the rate of positive culture was less than ours. Karlsson et al18 also reported of significantly higher PCT levels in positive culture cases compared to that of the negative ones.…”
supporting
confidence: 80%
“…Procalcitonin has been used widely as a biomarker of bacterial infection 17. However, previous studies reported PCT was not an indicator of organ dysfunction,18 particularly in the severe patient group, which could explain our result. Thus, IL‐6 may more accurately identify organ dysfunction severity than PCT or CRP.…”
Section: Discussioncontrasting
confidence: 57%
“…In patients with community-acquired pneumonia with decreased PCT from day one to day three, it was related to survival with 89% specificity, 82% negative predictive value and 71% positive predictive value 25 . Karlsson et al 12 showed in a recent study that mortality in patients with severe sepsis is smaller than in those whose PCT concentrations decreased by over 50% when compared to initial values. Claeys et al 13 , analyzing patients with septic shock, showed that after 48 hours of admission, PCT levels only decreased substantially in the surviving.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Most studies say that it is not possible to predict the outcome of critically ill patients based on high levels of PCT. Encouraging results were obtained from studies involving small numbers of patients and showed that serial determinations of PTC correlated with prognosis 12,13 . In recent studies, Guan et al 16 and Ruiz-Rodriguez et al 17 suggested, by analyzing small case series, that dynamic changes of PCT could be predictive of outcome in patients with severe sepsis and septic shock.…”
mentioning
confidence: 99%